Hubungan Perilaku Konsumsi Kopi dengan Kualitas Tidur pada Remaja di Kopi Janji Jiwa Depok Dua Timur Tahun 2022 - Tresnawulan, Syafa; Afrina, Rina; Kamilah, Siti (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Individuals who consume coffee may result in decreased sleep quality. Poor sleep quality can also cause negative psychological impacts on humans such as stress, depression, anxiety, lack of concentration and ineffective coping and also sleep quality. This study is to determine the relationship between coffee consumption behavior and sleep quality in adolescents at Kopi Janji Jiwa Depok Dua Timur. This research design uses quantitative with a cross sectional approach. The sample used was adolescents who consumed coffee totaling 60 respondents. The sampling technique is accidental sampling. Using the PSQI questionnaire and modified questionnaire with googel form. Statistical tests using the Chi - Square Test. Based on the results of the chi-square test, the Pvalue result is 0.12 (P <0.05). There is a relationship between coffee consumption behavior and sleep quality in adolescents at Kopi Janji Jiwa.